Alpha-cyclodextrin inhibits cholesterol crystal-induced complement-mediated inflammation: A potential new compound for treatment of atherosclerosis. (April 2019) - Pilely, Katrine; Bakke, Siril S.; Palarasah, Yaseelan; Skjoedt, Mikkel-Ole; Bartels, Emil D.; Espevik, Terje; Garred, Peter
Abstract: Background and aims: Cholesterol crystal (CC)-induced inflammation is a critical step in the development of atherosclerosis. CCs activate the complement system and induce an inflammatory response resulting in phagocytosis of the CCs, production of reactive oxygen species (ROS) and release of cytokines. The cyclodextrin 2-hydroxypropyl-β-cyclodextrin has been found to reduce CC-induced complement activation and induce regression of established atherosclerotic plaques in a mouse model of atherosclerosis, thus inhibition of complement with cyclodextrins is a potential new strategy for treatment of inflammation during atherosclerosis. We hypothesized that other cyclodextrins, like α-cyclodextrin, may have related functions. Methods: The effect of cyclodextrins on CC-induced complement activation, phagocytosis, and production of ROS from granulocytes and monocytes was investigated by flow cytometry and ELISA. Results: We showed that α-cyclodextrin strongly inhibited CC-induced complement activation by inhibiting binding of the pattern recognition molecules C1q (via IgM) and ficolin-2. The reduced CC-induced complement activation mediated by α-cyclodextrin resulted in reduced phagocytosis and reduced ROS production in monocytes and granulocytes. Alpha-cyclodextrin was the most effective inhibitor of CC-induced complement activation, with the reduction in deposition of complement activation products being significantly different from the reduction induced by 2-hydroxypropyl-β-cyclodextrin. We also found that α-cyclodextrin was able to dissolve CCs. Conclusions: This study identified α-cyclodextrin as a potential candidate in the search for therapeutics to prevent CC-induced inflammation in atherosclerosis. Graphical abstract: Image 1 Highlights: Alpha-cyclodextrin (ACD) inhibits deposition of complement activation products on cholesterol crystals. ACD inhibits binding of C1q (via IgM) and ficolin-2 to cholesterol crystals. ACD inhibits phagocytosis and production of ROS in granulocytes and monocytes. ACD dissolves cholesterol crystals over time.